STUDI KELAYAKAN BISNIS PADA PRODUK RENGGINANG MBAK YUL SITUBONDO - Pratama, M. Risqi; Wahyudi, Wahyudi; Putri, Puspita; Sa'diah, Halimatus (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
This study reveals the success story of Mbak Yul, a rengginang producer in Semiring Village, Mangaran District, Situbondo Regency. Has developed its business significantly. This research tries to understand Mbak Yul's journey in starting and developing her rengginag production, as well as the factors that have helped her success. The research method involves in-depth interviews with Mbak Yul, observations at production locations, and analysis of economic data related to her business. The research results show that Mbak Yul's success is due to dedication, innovation in variations of rengginang flavors, and the use of online platforms to market her products. Rengginang Mbak Yul was founded in 2016, where this place became one unit from the start of production, showroom and residence. Mbak Yul's Rengginang production process is manual, so it requires a lot of labor to produce Rengginang. Apart from that, collaboration with local communications has also supported its business growth. Mbak Yul's success in the rengginang business provides inspiration for young entrepreneurs and micro business people to follow in her footsteps. This study provides insight into the business potential of rengginang and its important role in promoting traditional Situbondo culinary delights.